The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1103/physrevb.101.014442
|View full text |Cite
|
Sign up to set email alerts
|

Oriented propagation of magnetization due to chiral edge modes in Kitaev-type models

Abstract: Detecting chiral edge modes in topological materials has been intensively pursued in experiments. However, the phenomena caused by the modes are not yet elucidated theoretically. We study the dynamics of chiral spinon wave packets at the edge in Kitaev-type magnets. More precisely, by relying on the exact solvability of the models, we construct a spinon wave packet, localized edge magnetization, which shows oriented propagation along the edge, whose behavior is expected from the chiral character of the dispers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…, L x , where L x is the number of unit cells, from left to right. For this configuration, the gauge-field Majorana fermions included in the top and bottom spins at open edges, b z l,1 and b z l,N , can not form the Z 2 gauge fields (54)(55)(56)(57). Thus, the perturbative calculations within the vortex-free sector described in the previous section are not applicable to these sites.…”
Section: Model Set-upmentioning
confidence: 98%
“…, L x , where L x is the number of unit cells, from left to right. For this configuration, the gauge-field Majorana fermions included in the top and bottom spins at open edges, b z l,1 and b z l,N , can not form the Z 2 gauge fields (54)(55)(56)(57). Thus, the perturbative calculations within the vortex-free sector described in the previous section are not applicable to these sites.…”
Section: Model Set-upmentioning
confidence: 98%
“…In this paper, we address this issue by using the transfer matrix method [6,9,[30][31][32][33][34][35][36][37][38][39][40][41][42]. In general, the transfer matrix method is applicable regardless of the phase of the bulk, and thus is suitable for studying the bulk-boundary correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the exact solution of the boundary modes is accessible in only a few models. In this regard, in the previous work [42], we have developed the method to obtain the exact edge solutions of arbitrary tight-binding models whose transfer matrix has a form of 4 × 4 matrix. By using this method, we study two concrete examples of the TSMs in two dimensions, namely, the Qi-Wu-Zhang (QWZ)-type model [43] and the Haldane-type model [44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal transport experiments have been useful for identifying QSLs-especially topological QSLs, such as α − RuCl 3 in a magnetic field, where half-integer quantized thermal Hall conductance has been reported [28]. Theory and experiment of spin transport in QSLs or QSOLs is less well developed [29][30][31][32][33][34]. Chen et al [35] and Chatterjee et al [36] suggested that by sandwiching a QSL material between two paramagnetic metals and driving a spin current through the structure, one could characterize different types of QSLs as they have different power laws of spin current I s − V s relation.…”
mentioning
confidence: 99%